Conflicting Roles of ZFP36L1 in Regulating the Progression of Muscle Invasive Bladder Cancer - Yuan, Simin; Zhai, Yujia; Tao, Tao; Zhang, Xiaolong; Bashir, Ghassan; Li, Guangzhi; Wang, Gang; Wu, Song (Frontiers in Molecular Biosciences, 2022)
As the most common carcinoma of the human urinary system, bladder cancer (BC) is characterized by high recurrence, and poor prognosis after metastasis. In the past decade, genome-wide expression and sequencing studies had identified key genes and pathways related to BC, and pictured the comprehensive molecular features of the disease. Our previous study indicated that the coding gene of zinc finger protein 36 like 1 (ZFP36L1) mutated frequently in bladder tumor tissues and may be a potential suppressor for BC. The present study aimed to further investigate the role of ZFP36L1 in BC, and the survival analysis based on TCGA dataset revealed that high expressing level of ZFP36L1 associated with poorer prognosis of the patients with muscle invasive bladder cancer (MIBC). The associations of ZFP36L1 expression to the clinicopathological and molecular biological features also implicated the high level of ZFP36L1 may related to worse outcomes of patients. Also, GSEA indicated that high expression of ZFP36L1 significantly associated with enhanced activity of cancer metastasis related pathways. Functions of ZFP36L1 in MIBC were investigated further, and it was found that while ZFP36L1 suppressed the self-renewal of bladder cancer cells, it promoted the invasiveness of the cells markedly. Taken together, these results led to the conflicting roles of ZFP36L1 in regulating the progression of MIBC, and revealed further researches are needed to clarify the functions of the gene in tumor initiation and recurrence.